2012
DOI: 10.1038/ncomms1892
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of CD44 mRNA by ESRP1 enhances lung colonization of metastatic cancer cell

Abstract: In cancer metastasis, various environmental stressors attack the disseminating cells. The successful colonization of cancer cells in secondary sites therefore requires the ability of the cells to avoid the consequences of such exposure to the stressors. Here we show that orthotopic transplantation of a CD44 variant isoform-expressing (CD44v + ) subpopulation of 4T1 breast cancer cells, but not that of a CD44v − subpopulation, in mice results in efficient lung metastasis accompanied by expansion of stem-like ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
319
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(335 citation statements)
references
References 53 publications
(72 reference statements)
14
319
2
Order By: Relevance
“…Among the downregulated genes in treated tumors, were the metastasis-suppressor gene NDRG1 (23) and the adhesion molecule EPCAM, a regulator of the alternative splicing of CD44 (ESRP1; ref. 24) and ST14 (a negative regulator of the EMT mediator ZEB1; Table 2; Fig. 1A; ref.…”
Section: Differential Gene Expression Between Treated and Nontreatedmentioning
confidence: 99%
“…Among the downregulated genes in treated tumors, were the metastasis-suppressor gene NDRG1 (23) and the adhesion molecule EPCAM, a regulator of the alternative splicing of CD44 (ESRP1; ref. 24) and ST14 (a negative regulator of the EMT mediator ZEB1; Table 2; Fig. 1A; ref.…”
Section: Differential Gene Expression Between Treated and Nontreatedmentioning
confidence: 99%
“…The overexpression of ESRP1 has been reported to cause a splicing switch from CD44s to CD44v (18)(19)(20). In order to examine the differential roles of CD44s and CD44v8-10 in bone metastases, the current study employed an approach in which the ESRP1 gene was stably transduced into MDA-MB-231 human breast cancer cells and A549 human lung cancer cells (MDA/ESRP1 and A549/ESRP1, respectively).…”
Section: Effects Of Esrp1 Overexpression On Bone Metastases Esrp1mentioning
confidence: 99%
“…is an epithelial-specific splicing factor that regulates the alternative splicing of several genes, including CD44 (18)(19)(20). The overexpression of ESRP1 has been reported to cause a splicing switch from CD44s to CD44v (18)(19)(20).…”
Section: Effects Of Esrp1 Overexpression On Bone Metastases Esrp1mentioning
confidence: 99%
“…Tissue specific alternative splicing is usually regulated by a combination of tissue-specific and ubiquitously expressed splicing factors (Pan et al, 2008;Sultan et al, 2008;Chen and Manley, 2009;Bland et al, 2010) and has been demonstrated to play an important role in regulation of tissue-specific protein interaction networks (Buljan et al, 2012). In addition, mis-regulated alternative RNA splicing events have a significant role in human diseases, cell cycle, and cell death (Hallegger et al, 2010;Gang et al, 2011;Honda et al, 2012;Raghavachari, 2012;Yae et al, 2012). For example, a specific isoform of pyruvate kinase resulting from hnRNP-mediated mRNA alternative splicing is required for tumor cell proliferation .…”
Section: Regulation Of Alternative Rna Splicingmentioning
confidence: 99%